Variation in spatial dependencies across the cortical mantle discriminates the functional behaviour of primary and association cortex - Robert Leech; Reinder Vos De Wael; František Váša; Ting Xu; R. Austin Benn; Robert Scholz; Rodrigo M. Braga; Michael P. Milham; Jessica Royer; Boris C. Bernhardt; Emily J. H. Jones; Elizabeth Jefferies; et al. (Nature Communications, 2023)
Abstract Recent theories of cortical organisation suggest features of function emerge from the spatial arrangement of brain regions. For example, association cortex is located furthest from systems involved in action and perception. Association cortex is also ‘interdigitated’ with adjacent regions having different patterns of functional connectivity. It is assumed that topographic properties, such as distance between regions, constrains their functions, however, we lack a formal description of how this occurs. Here we use variograms, a quantification of spatial autocorrelation, to profile how function changes with the distance between cortical regions. We find function changes with distance more gradually within sensory-motor cortex than association cortex. Importantly, systems within the same type of cortex (e.g., fronto-parietal and default mode networks) have similar profiles. Primary and association cortex, therefore, are differentiated by how function changes over space, emphasising the value of topographical features of a region when estimating its contribution to cognition and behaviour.